Credit Policy and Performance of Commercial Banks in Kampala, Uganda: A Case Study of Post Bank Uganda (PBU), Main Branch - Derick Atumanya (Uganda Christian University, 2025)
The stability and growth of the Ugandan economy are significantly influenced by the performance of its commercial banking sector. A well structured credit policy is a critical management tool for mitigating risk, ensuring loan portfolio quality and ultimately determining a bank's financial performance. This study investigates the relationship between credit policy and performance of commercial banks with a specific focus on Post Bank Uganda's main branch in Kampala. The research adopted a case study design, utilizing a mixed methods approach. Primary data was collected through questionnaires administered to a sample of staff at Post Bank Uganda's main branch and interviews with key management personnel. Financial performance was measured using key indicators such as Return on Assets (ROA), Return on Equity (ROE) and the level of Non Performing Loans (NPLs). Data was analyzed using both descriptive and inferential statistics. The study found that specific components of Post Bank Uganda's credit policy have a statistically significant and positive relationship with the bank's performance. A well defined credit policy was shown to contribute to higher profitability (as measured by ROA and ROE). The research also identified external economic factors and stringent loan appraisal processes as influential elements impacting the effectiveness of the credit policy The study concludes that a robust and effectively implemented credit policy is a fundamental driver of improved financial performance for commercial banks in Uganda. It enhances asset quality, maximizes returns, and minimizes credit losses. It is recommended that Post Bank Uganda, and similar financial institutions continuously review and adapt their credit policies to align with dynamic market conditions invest in advanced credit risk assessment technologies and enhance staff training in credit management to sustain and improve performance. Keywords: Credit Policy, Financial Performance, Commercial Banks, Non Performing Loans, Return on Assets, Post Bank Uganda, Kampala.